Pyrrolyl 4-quinolone alkaloids from the mangrove endophytic fungus Penicillium steckii SCSIO 41025: Chiral resolution, configurational assignment, and enzyme inhibitory activities. (June 2021) - Chen, Chun-Mei; Chen, Wei-Hao; Pang, Xiao-Yan; Liao, Sheng-Rong; Wang, Jun-Feng; Lin, Xiu-Ping; Yang, Bin; Zhou, Xue-Feng; Luo, Xiao-Wei; Liu, Yong-Hong
Abstract: Six undescribed 4-quinolone alkaloids, including four racemic mixtures, (±)-oxypenicinolines A−D, and two related ones, penicinolines F and G, together with seven known analogues, were isolated from the mangrove-derived fungus Penicillium steckii SCSIO 41025 (Trichocomaceae). The racemates were separated by HPLC using chiral columns. Their structures including absolute configurations were elucidated by extensive spectroscopic analysis, electronic circular dichroism (ECD) experiments, and single-crystal X-ray diffraction analysis. Structurally, (±)-oxypenicinolines A−D shared with an unusual 6/6/5/5 tetracyclic system incorporating a rare tetrahydro-pyrrolyl moiety. A plausible biosynthetic pathway for pyrrolyl 4-quinolone alkaloids is proposed. (±)-oxypenicinoline A and quinolactacide displayed α -glucosidase inhibitory activity with the IC50 values of 317.8 and 365.9 μ Μ, respectively, which were more potent than that of acarbose (461.0  μ M). Additionally, penicinoline and penicinoline E showed weak inhibitions toward acetylcholinesterase (AChE). Graphical abstract: A pair of unprecedented enantiomeric pyrrolyl 4-quinolone alkaloids, (±)-oxypenicinoline A (1 ), were isolated from the mangrove-derived fungus Penicillium steckii SCSIO 41025 with α-glucosidase inhibitory activity. Image 1 Highlights: Six previously undescribed 4-quinolone alkaloids were isolated from Penicillium steckii. (±)-Oxypenicinolines A−D are the first four cases of enantiomeric PQAs sharing an α -oxidized tetrahydro-pyrrolyl moiety from nature. Structures and configurations of these separated enantiomers are confirmed by single-crystal X-ray diffraction analysis and ECD calculations. A plausible biosynthetic pathway is proposed. (±)-Oxypenicinoline A and quinolactacide displayed inhibitory activity against α -glucosidase.